Teamwork Assessment and Self/Peer Evaluation in Higher Education - Issa, Tomayess (IGI Global, 2014)
This chapter examines the challenges and opportunities associated with fostering students’ learning skills through teamwork assessment and self/peer evaluation in the Business Technology 2 (BT2) undergraduate unit at an Australian university. This assessment will encourage students to promote skills in teamwork, communication (writing, interpersonal interaction and cultural awareness, and presenting), critical and creative thinking (problem-solving and solving and decision-making), Information Technology literacy, and information literacy, and is intended to increase their self-confidence in both their studies and in the future workforce. This chapter provides empirical evidence from 267 students, based on quantitative and qualitative data derived from two sources. The first consists of anonymous informal feedback collected during the semester, while the second (formal) source of students’ evaluations and attitudes towards the BT2 unit and teaching is “eVALUate.” The students indicate that they are satisfied with this form of assessment as it assists them to develop specific skills and understandings, including time management, problem solving, decision-making, cultural awareness, oral presentation, communication, and meeting a deadline.